2013
DOI: 10.1073/pnas.1307617110
|View full text |Cite
|
Sign up to set email alerts
|

The gated induction system of a systemic floral inhibitor, antiflorigen, determines obligate short-day flowering in chrysanthemums

Abstract: Photoperiodic floral induction has had a significant impact on the agricultural and horticultural industries. Changes in day length are perceived in leaves, which synthesize systemic flowering inducers (florigens) and inhibitors (antiflorigens) that determine floral initiation at the shoot apex. Recently, FLOWERING LOCUS T (FT) was found to be a florigen; however, the identity of the corresponding antiflorigen remains to be elucidated. Here, we report the identification of an antiflorigen gene, Anti-florigenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 39 publications
5
117
1
Order By: Relevance
“…potato and tomato inhibit expression of the SINGLE FLOWER TRUSS (SFT) florigen and of StSP6A, respectively (Abelenda et al, 2016;Soyk et al, 2017). Similar modules in which an FT-like protein inhibits developmental transitions by repressing a second FT-like gene have been reported also for flowering in sugar beet (Pin et al, 2010;Higuchi et al, 2013) and bulbing in onion (Allium cepa; Lee et al, 2013). In rice, both autoregulatory and relay mechanisms between Hd3a and RFT1 are possible under inductive conditions, when both proteins are expressed.…”
Section: The Rice Florigens Act In Leaves To Regulate Their Own Exprementioning
confidence: 74%
See 1 more Smart Citation
“…potato and tomato inhibit expression of the SINGLE FLOWER TRUSS (SFT) florigen and of StSP6A, respectively (Abelenda et al, 2016;Soyk et al, 2017). Similar modules in which an FT-like protein inhibits developmental transitions by repressing a second FT-like gene have been reported also for flowering in sugar beet (Pin et al, 2010;Higuchi et al, 2013) and bulbing in onion (Allium cepa; Lee et al, 2013). In rice, both autoregulatory and relay mechanisms between Hd3a and RFT1 are possible under inductive conditions, when both proteins are expressed.…”
Section: The Rice Florigens Act In Leaves To Regulate Their Own Exprementioning
confidence: 74%
“…Such approach has led to the identification of a loop regulating StSP6A expression, encoding a tuberigen, the mobile protein causing tuber formation at the apical meristem of potato stolons, and sharing high sequence similarity with Hd3a (Navarro et al, 2011). A similar autoregulatory loop in the expression of an endogenous florigen has been recently reported in Chrysanthemum, where transcriptional ½AQ3 induction of CsFTL3 required a complex formed by CsFTL3 and CsFDL1 proteins (Higuchi et al, 2013). It is noteworthy that regulatory loops involving two FT-like proteins are also very common among Angiosperms.…”
Section: The Rice Florigens Act In Leaves To Regulate Their Own Exprementioning
confidence: 83%
“…In chrysanthemum photoperiodic manipulation of flowering is a common practice, where transgenics with altered flowering time are needed to maintain year-round flower supply and for which study of genes governing photoperiodic response in chrysanthemum is imperative. Higuchi et al 55 identified an antiflorigen gene, Anti-florigenic FT/TFL1 family protein (AFT) from a wild chrysanthemum (Chrysanthemum seticuspe), whose expression is mainly induced in leaves under non-inductive conditions. A transient gene expression assay indicated that CsAFT inhibits flowering by directly antagonizing the flowerinductive activity of CsFTL3, a C. seticuspe ortholog of FT (FLOWERING LOCUS T), through interaction with CsFDL1, a basic leucine zipper (bZIP) transcription factor FD homolog of Arabidopsis.…”
Section: Chrysanthemum (Dendranthema Grandiflora)mentioning
confidence: 99%
“…Also using Illumina technology, Xu et al (2013) performed large-scale transcriptome sequencing of chrysanthemum plants under dehydration stress. A Japanese research team recently detected genes encoding florigens and antiflorigens, the key regulators of photoperiodic flowering in chrysanthemum, using the wild diploid chrysanthemum C. seticuspe (Higuchi et al, 2013;Oda et al, 2012). Information from wild diploid species should help resolve the genetic complexity of chrysanthemum and contribute to genetic analysis of important traits, map-based gene cloning, and efficient breeding of polyploid cultivars.…”
Section: Chrysanthemummentioning
confidence: 99%